2021
DOI: 10.1002/admi.202101039
|View full text |Cite
|
Sign up to set email alerts
|

Semi‐Automatic Deposition of Oriented Cu(OH)2 Nanobelts for the Heteroepitaxial Growth of Metal–Organic Framework Films

Abstract: Processing oriented metal–organic frameworks (MOFs) as thin films is a key challenge for their application to device fabrication. However, typical fabrication methods cannot generate precisely oriented crystals on commercially relevant scales (i.e., cm2). This limits access to applications that require anisotropic functional properties (e.g., separation, optics, and electronics). Currently, highly oriented copper‐based MOFs are synthesized via the addition of the organic MOF component to an ethanolic solution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 28 publications
(42 reference statements)
0
27
0
Order By: Relevance
“…S2(d) †). 41 To evaluate the porosity, the DMOF-1-on-Cu 2 BDC 2 -on-Cu(OH) 2 lm was deposited on a quartz crystal microbalance (QCM), where the resonance frequency change of each MOF layer was measured upon exposure to methanol vapor (Fig. S3(a) †).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…S2(d) †). 41 To evaluate the porosity, the DMOF-1-on-Cu 2 BDC 2 -on-Cu(OH) 2 lm was deposited on a quartz crystal microbalance (QCM), where the resonance frequency change of each MOF layer was measured upon exposure to methanol vapor (Fig. S3(a) †).…”
Section: Resultsmentioning
confidence: 99%
“…The lower MOF layer comprises the oriented Cu 2 BDC 2 structure grown on the Cu(OH) 2 nanobelt film, which is fabricated by following the secondary heteroepitaxial growth strategy 38 based on an automated nanobelt deposition procedure. 41 The subsequent DMOF-1 growth occurs by matching its crystal lattice with the lower Cu 2 BDC 2 -on-Cu(OH) 2 layer ( Fig. 1(b and c) ) 38 and is obtained by following a two-step method: Firstly, the Zn(acetate) 2 nodes are covalently attached to the loose carboxylate groups of the Cu 2 BDC 2 -on-Cu(OH) 2 layer, which is then followed by converting the film in a methanolic linker solution (H 2 BDC = terephthalic acid, DABCO = 1,4-diazabicyclo[2.2.2]octane).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mixed-linker MOF films were prepared by depositing aligned Cu(OH)2 nanobelts (NBs) on a silicon substrate according to our previously reported protocol (see SI for details). [13] The Cu(OH)2 NB films were then immersed in 10 mL of a methanolic solution containing DABCO and the dicarboxylate linkers Br2BDC and BDC in different molar ratios to yield a set of films composed of Cu2[(Br2BDC)x(BDC)1-x]2DABCO (x = Br2BDC/(BDC + Br2BDC). We will refer to these samples according to the nominal mole ratio of the dicarboxylate ligands, e.g., B0 for x = 0, B94 for x= 0.94, and B100 for x=1.…”
Section: Synthesis Of Cu2l2dabco Films (L = Bdc/br2bdc)mentioning
confidence: 99%
“…To this end, a recent and significant advance in MOF film research [12] showed that oriented polycrystalline MOF films can be prepared at commercially relevant scales. [13] These films were synthesized from pre-aligned metal hydroxide nanostructures (Cu(OH)2 nanobelts (NBs)) where the ceramic material simultaneously acts as a metal source and directs epitaxial growth of the aligned MOF crystals.…”
Section: Introductionmentioning
confidence: 99%